Rice Glycosyltransferase Gene UGT85E1 Is Involved in Drought Stress Tolerance Through Enhancing Abscisic Acid Response - Liu, Qian; Dong, Guang-rui; Ma, Yu-qing; Zhao, Shu-man; Liu, Xi; Li, Xing-kun; Li, Yan-jie; Hou, Bing-kai (Frontiers in Plant Science, 2021)
Drought is one of the most important environmental constraints affecting plant growth and development and ultimately leads to yield loss. UDP-dependent glycosyltransferases (UGTs) are believed to play key roles in coping with environmental stresses. In rice, it is estimated that there are more than 200 UGT genes. However, most of them have not been identified toward their physiological significance. In this study, we reported the characterization of a putative glycosyltransferase gene UGT85E1 in rice. UGT85E1 gene is significantly upregulated by drought stress and ABA treatment. Overexpression of UGT85E1 led to enhanced tolerance in transgenic rice plants to drought stress, while the ugt85e1 mutants of rice showed more sensitive phenotype to drought stress. Further studies indicated that UGT85E1 overexpression induced ABA accumulation, stomatal closure, enhanced ROS scavenging capacity, increased proline and sugar contents and upregulated expression of stress-related genes under drought stress condition. Moreover, when UGT85E1 was ectopically overexpressed in Arabidopsis, the transgenic plants showed increased tolerance to drought as well as in rice. Our findings suggest that UGT85E1 plays an important role in mediating plant response to drought and oxidative stresses. This work may provide a promising candidate gene for cultivating drought tolerant crops both in dicots and monocots.